Concurrent tellurite reduction, biogenesis of elemental tellurium nanostructures and biological nutrient removal in aerobic granular sludge sequencing batch reactor. Issue 6 (December 2022) - Sarvajith, M.; Nancharaiah, Y.V.
Abstract: This study investigated the metabolic potential of aerobic granular sludge (AGS) to simultaneously remove tellurium oxyanion (tellurite, TeO3 2- ), COD, ammonium-nitrogen and phosphorus in a sequencing batch reactor (SBR). AGS readily converted soluble and toxic tellurite to biogenic elemental tellurium (Bio-Te 0 ) by following first-order reaction. Bio-Te 0 was dark black in colour and largely entrapped in the granules. Although endogenous substrates acted as source of electrons for tellurite reduction, it was sustained by supplying exogenous electron donor. A lab-sale SBR was seeded with AGS and operated at varied initial tellurite concentrations for 185 days to investigate tellurite reduction and biological nutrient removal (BNR). Stable removal efficiencies of > 98% Te was achieved from simulated wastewater containing 0.01–1 mM tellurite. Soluble tellurite was converted to Bio-Te 0 and retained in the AGS. SEM-EDS, XRD and Raman spectroscopy confirmed formation of Bio-Te 0 and its association with the granules. Enrichment of Bacteroidia, Petrimonas sp. and several other tellurite-reducing bacteria was confirmed by 16S rRNA gene sequencing. Enrichment of ammonium oxidizing bacteria, elimination of nitrite oxidizing bacteria and profiles of reactive-nitrogen compounds suggested occurrence of nitriation-denitriation pathway. Although ammonium removal was inhibited by tellurite, recovery occurred much quickly in the presence of up to 0.1 mM tellurite. Higher P removal under tellurite-reducing condition was linked to hydroxyapatite precipitation as confirmed by EDS and P-fractionation. Efficient BNR under toxic pollutant conditions and excellent metal(loid) immobilization capabilities implicate prospective use of AGS technology in metal-laden waste management and metal(loid) biorecovery applications. Graphical Abstract: ga1 Highlights: Complete, sustained and lactate-dependent conversion of up to 175 mg/L Te IV to Te 0 Biogenic Te 0 nanostructures were associated with aerobic granular sludge. Partial inhibition of ammonium removal and lower abundance of AOB by Te IV . Efficient nitrogen removal via nitritation-denitritation at different initial Te IV loadings. Higher P-removal in Te IV -fed reactor due to hydroxyapatite precipitation.